Implementasi Pemberian Aromaterapi Lavender untuk Mengurangi Nyeri Post Sectio Caesarea di Ruang Haji RSI Banjarnegara: Case Study - Umu Hani; Susilo Rudatin; Swasti Jamalina; Ikit Netra (Journal of Bionursing, 2022)
Background : Labor is the process of expulsion of the fetus that occurs during a full-term pregnancy, with the expulsion of the placenta and membranes. Problems during saecarea due to tearing of tissue after a cesarean section may cause pain due to surgery. Objectives: This study aims to describe nursing care of patients with disturbed pain comfort Mrs. S With a Post Section Caesarea Medical Diagnosis at RSI Banjarnegara. Methods: This type of study is descriptive in the form of case studies. The sample used in this case study is Mrs. S with a sense of discomfort and pain disorder. The focus of the study discussed by the author is pain comfort disorders in postoperative sectio caesaria patients. Processing and analyzing data using descriptive analysis. Result: The three nursing diagnoses that have been established show that the acute pain associated with the physical injury agent is partially resolved, the other diagnoses that have been established have been resolved. Conclusion: Non-pharmacological therapy with Lavender aromatherapy can relieve Post Sectio Caesarea Pain